Wrinkle lip pattern in smokers and non-smokers for identification in forensic dentistry - Harqad, Teuku Muhammad; Dardjan, Murnisari; Hardjadinata, Ine Suhartina (Universitas Padjadjaran, 2014)
Introduction: Lip prints can be used as one of support for identification Because it has a pattern or lip wrinkles that never the same (unique) in each individual. Smoking has become a common habit and widespread in the community. Prolonged heat stimuli from smoking can cause changes in the lip wrinkles. Methods: This descriptive study found the description of lip print patterns on smokers and non-smokers. Samples Obtained as many as 30 people chosen by Certain criteria. Direct observation was made through some white cardboard that had been printed of lip prints and divided into four quadrants. Each quadrant was observed with a magnifying glass and count the number of lip wrinkles. Results: The number of lip wrinkles on each quadrant and been jotted in a table. The result is varied in the number of lip wrinkles in each quadrant between the smokers and non-smokers. Conclusion: The lip prints pattern of smokers showed a result of 12 to 17 pieces of wrinkles, and the lip prints pattern of non-smokers have 8 to 12 lines of wrinkles.